STRUKTUR DAN KOMPOSISI JENIS VEGETASI DI HUTAN SEKUNDER: STUDI KASUS KHDTK LABANAN PROVINSI KALIMANTAN TIMUR (Structure And Species Composition Of Tree In Secondary Forest: A case study at KHDTK Labanan, East Borneo Province) - Karmilasanti Karmilasanti; M. Fajri (Jurnal Penelitian Hutan Tanaman, 2020)
ABSTRACT Unproductive forests in the form of secondary forest tend to be converted into forest plantation, agriculture and other land uses. Even though the secondary forest can still be restored using native commercial species. This study aimed to determine the structure and composition of stands, the potential of residual stands, and natural regeneration of the secondary forest in KHDTK Labanan. The research was carried out through vegetation inventory and vegetation analysis to calculate stand potential, natural regeneration, Importance Value Index (IVI), and species diversity. The results showed the structure of commercial species stands in secondary forests in the Labanan KHDTK followed an inverted "J" shaped exponential curve as well as stand structure of natural forest. The potential of commercial species stands with diameter of 20 cm and above was 22.30 m3/ha with a number of trees more than 25 trees/ha. Natural regeneration of commercial species for pole were 121 stems/ha, sapling were 47 stems/ha, and seedling were 50 stems/ha. The dominant species of native commercial such as  Shorea parvifolia, S. atrinervosa, S. agami, S. hopeifolia, Madhuca malaccensis, and Koilodepas sp needs to be maintained and nurtured in order to ensure the continuity the natural succession and diversity, thus become a source of seed trees. The species diversity index in the sekunder forest was high to moderate.                                                 ABSTRAK Hutan tidak produktif berupa hutan sekunder cenderung dikonversi menjadi hutan tanaman, perkebunan, dan peruntukkan lainnya, meskipun hutan sekunder masih bisa dipulihkan dengan menggunakan jenis-jenis komersial setempat. Penelitian ini bertujuan untuk mengetahui struktur dan komposisi tegakan, potensi tegakan tinggal, dan permudaan alami pada hutan sekunder di KHDTK Labanan. Penelitian dilakukan melalui inventarisasi vegetasi dan analisis vegetasi guna menentukan potensi tegakan, kondisi permudaan alami, Indeks Nilai Penting (INP), dan keragaman jenis. Hasil penelitian menunjukkan struktur tegakan jenis komersial pada hutan sekunder di KHDTK Labanan mengikuti kurva eksponensial berbentuk “J” terbalik seperti struktur tegakan pada berbagai kondisi hutan alam. Potensi tegakan jenis komersial diameter 20 cm ke atas sebesar 22,30 3m/ha dengan jumlah pohon lebih dari 25 pohon/ha. Permudaan alami jenis komersial untuk tingkat tiang 121 pohon/ha, pancang 47 batang/ha, dan semai 50 batang/ha. Dengan demikian, pada hutan sekunder KHDTK Labanan tidak diperlukan pengayaan. Jenis unggulan setempat yang dominan antara lain jenis Shorea parvifolia, S. atrinervosa, S. agami,  S. hopeifolia, Madhuca malaccensis, dan Koilodepas sp. perlu dijaga dan dipelihara agar suksesi alami dan keanekaragaman terus berlanjut, serta menjadi sumber benih. Indeks keanekaragaman jenis di hutan sekunder KHDTK Labanan termasuk tinggi sampai sedang.